L'extrait aqueux lyophilisé de Portulaca oleracea prévient contre la peroxydation lipidique en augmentant l'activité de la paraoxonase-1 sérique, chez des rats soumis à un régime enrichi en cholestérol [Aqueous extract of Portulaca oleracea prevents lipid peroxidation and increases serum paraoxonase-1 activity, in rats fed cholesterol enriched-diet] - Yahiaoui ZIDAN; Sherazede BOUDERBALA; Malika BOUCHENAK (Nutrition & Santé, 2016)
Introduction. Many studies have shown the effect of medicinal plants on the reduction of lipids and their peroxidation, and on the increase of paraoxonase-1 (PON-1) activity, in hypercholesterolemic rat. Objective. The aim of this study was to determine the effect of aqueous extract of Portulaca oleracea (Po) on serum and lipoproteins lipid peroxidation as well as serum PON-1 activity, in hypercholesterolemic rats. Material and methods. Male Wistar rats (n=12) were fed on 1% cholesterol- enriched diet for 10 days. After this adaptation phase, hypercholesterolemic rats (total cholesterol (TC) = 5.66±1.60 mmol/L) were divided into two groups submitted to the same diet and treated or not with Po for 28 days. Results. Hypercholesterolemic rats treated with Po were compared to untreated hypercholesterolemic rats. Serum TC, VLDL-C and LDL-HDL1-C were decreased respectively by 45%, 42% and 58%. HDL-C (HDL2 + HDL3) was increased by 34%, in Po-HC group. Lipid peroxidation evaluation showed decreased thiobarbituric acid reactive substances concentrations in serum (-16%), VLDL (-48%), LDL-HDL1 (-32%), HDL2 (-16%) and HDL3 (-41%). Serum PON-1 activity was 1.9-fold higher, in treated than untreated hypercholesterolemic groups. Conclusion. In hypercholesterolemic rat, it appears that treatment with Po aqueous extract induces hypocholesterolemic effect. Po reduces lipid peroxidation in serum and lipoproteins by increasing serum PON-1 activity.